Bank of Japan's exchange-traded fund purchases as an unprecedented monetary easing policy - Sayuri Shirai (Asian Development Bank Institute (ADBI), 2018)
This paper highlights exchange-traded funds (ETF) purchases conducted by the Bank of Japan under Quantitative and Qualitative Monetary Easing with Yield Curve Control. The policy to indirectly purchase stocks is unprecedented in terms of the scale and duration among major central banks. The purpose of this policy is to promote portfolio rebalancing among individuals in addition to achieving the 2% price stability target. While stock prices have more than doubled, individuals have remained largely risk-averse and foreign investors have increasingly dominated the stock market. Moreover, the BOJ has become one of the largest (silent) investors, with growing impacts on stock prices through reducing downside risk and possibly overvaluing some small-cap listed firms. Given that achieving 2% inflation is a distant future prospect, the BOJ may find it necessary to gradually unwind the policy by purchasing ETFs only when the stock market is under severe stress, and thereby reduce the annual pace of ETF purchases from about ¥6 trillion. This view is in line with the BOJ's adjustments announced in July 2018 on introducing flexibility and changing the composition of ETF purchases. Whether the BOJ will be able to take a clearer, more decisive step remains to be seen.
Keywords: E52; E58; 330; exchange-traded funds; price-earnings ratio; bubbles; corporate governance; portfolio rebalance